Antibacterial activity and mechanism of action of bacteriocin LFX01 against Staphylococcus aureus and Escherichia coli and its application on pork model. (February 2023) - Xin, Wei-Gang; Wu, Gang; Ying, Jian-Ping; Xiang, Yi-Zhou; Jiang, Yu-Hang; Deng, Xian-Yu; Lin, Lian-Bing; Zhang, Qi-Lin
Abstract: Antibacterial activity and mechanism of action of bacteriocins against bacteria that cause pork contamination remain unclear. Here, antibacterial activity of bacteriocin LFX01 against two important indicator strains ( i.e., Staphylococcus aureus and Escherichia coli ) and its mechanism of action were investigated. The results showed antibacterial activity of LFX01 against growth and biofilm formation of S. aureus _26 (strain 2612:1606BL1486) and E. coli _02 (strain CMCC(B)44102). Additionally, the results demonstrated that LFX01 could decrease cell metabolic activity, disrupt cell membrane permeability and integrity, and trigger leakage of intracellular contents ( e.g., K +, ATP, and lactic dehydrogenase). Furthermore, gel retardation showed that LFX01 could bind to the genomic DNA of indicator strains, disrupting DNA structure. These results uncovered mechanism of action of LFX01 against indicator strains from physiological and phenotypic levels. When applied to the surface of fresh pork models, the antibacterial activity of LFX01 against indicator strains was further confirmed. These findings suggested that LFX01 could be a potential pork preservative for controlling foodborne pathogens. Highlights: LFX01 has antibacterial activity against S. aureus and E. coli . LFX01 triggered leakage of intracellular contents, and disrupted cell metabolic activity and DNA structure. LFX01 significantly inhibited S. aureus and E. coli on raw pork. LFX01 could be a potential pork preservative.